2015
DOI: 10.1037/pspi0000014
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects of perceived emotional synchrony in collective gatherings.

Abstract: In a classic theory, Durkheim (1912) predicted that because of the social sharing of emotion they generate, collective gatherings bring participants to a stage of collective effervescence in which they experience a sense of union with others and a feeling of empowerment accompanied by positive affect. This would lead them to leave the collective situation with a renewed sense of confidence in life and in social institutions. A century after Durkheim's predictions of these effects, though, they remained unteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
409
3
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(466 citation statements)
references
References 71 publications
32
409
3
22
Order By: Relevance
“…With this heightened processing, a person's emotional state becomes intensified and then translated as a joint experience shared among those belonging to the same group and participating in the same ritual (Shteynberg, Hirsh, Galinsky, & Knight, 2014;see Shteynberg, 2015). For example, research found that people expressed stronger feelings of fusion with their group after participating in a group walking ritual, and this was mediated by the extent to which they perceived emotional synchrony with other walkers (Páez et al, 2015). Similar research found that people enjoy the holiday seasons more when engaging in holiday rituals with others (vs. alone) because the ritualistic experiences heighten people's attention and shared involvement in the moment (Sezer, Norton, Gino, & Vohs, 2016).…”
Section: Affiliating With Group Members: Performing Collective Ritualsmentioning
confidence: 50%
See 3 more Smart Citations
“…With this heightened processing, a person's emotional state becomes intensified and then translated as a joint experience shared among those belonging to the same group and participating in the same ritual (Shteynberg, Hirsh, Galinsky, & Knight, 2014;see Shteynberg, 2015). For example, research found that people expressed stronger feelings of fusion with their group after participating in a group walking ritual, and this was mediated by the extent to which they perceived emotional synchrony with other walkers (Páez et al, 2015). Similar research found that people enjoy the holiday seasons more when engaging in holiday rituals with others (vs. alone) because the ritualistic experiences heighten people's attention and shared involvement in the moment (Sezer, Norton, Gino, & Vohs, 2016).…”
Section: Affiliating With Group Members: Performing Collective Ritualsmentioning
confidence: 50%
“…Longitudinal and experimental designs, however, provide more convincing support for the notion that engaging in collective rituals helps a person affiliate with fellow group members. For example, people who walked together in the Tamborrada ritual in Spain reported more group belonging and social integration after the event than before (Páez et al, 2015). In addition, people donated more money to their temple after participating in a high-ordeal Hindu ritual compared with a low-ordeal ritual, and the level of pain correlated with the amount of donation .…”
Section: Affiliating With Group Members: Performing Collective Ritualsmentioning
confidence: 91%
See 2 more Smart Citations
“…Sharing pain collectively with others promotes cooperation and prosociality (Bastian, Jetten, & Ferris, 2014;Xygalatas et al, 2013). Collective enjoyment and pleasure also binds groups together -referred to as collective effervescence or communitas (Durkheim, 1912(Durkheim, /1995Páez, Rimé, Basabe, Wlodarczyk, & Zumeta, 2015;E. Turner, 2012;V.…”
Section: Sharing Pain -And Pleasurementioning
confidence: 99%